1994
DOI: 10.1002/1097-0142(19941001)74:7<1945::aid-cncr2820740720>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Ondasetron versus granisetron in the prevention of chemotherapy-induced nausea and vomiting. Results of a prospective randomized trial

Abstract: Background. A single‐institution, prospective, randomized open trial was performed to compare ondansetron and granisetron in the prevention of chemotherapyrelated nausea and vomiting. The effect of antemetic drugs was analyzed indipendently for patients treated with highly emetogenic chemotherapy (Study 1), and those treated with moderately emetogenic regimens (Study 2). Methods. In Study 1. 182 patients treated with chemotherapeutic regimens containing high dose cisplatin (more than 70 mg/m2) were randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…Comparison of granisetron with ondansetron in Western studies showed that the former had either equal or greater efficacy (Jantunen et al, 1993;Gebbia et al, 1994;Noble et al, 1994;Ruff et al, 1994;Navari et al, 1995;Mantovani et al, 1996). To our knowledge, no study comparing these two agents in Oriental patients has been reported before.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Comparison of granisetron with ondansetron in Western studies showed that the former had either equal or greater efficacy (Jantunen et al, 1993;Gebbia et al, 1994;Noble et al, 1994;Ruff et al, 1994;Navari et al, 1995;Mantovani et al, 1996). To our knowledge, no study comparing these two agents in Oriental patients has been reported before.…”
mentioning
confidence: 89%
“…single dose. Five subsequent randomized trials showed no significant difference in the antiemetic efficacy between intravenous granisetron and ondansetron (Gebbia et al, 1994;Noble et al, 1994;Ruff et al, 1994;Navari et al, 1995;Mantovani et al, 1996). These studies compared the two agents in patients receiving cisplatin-based highly emetogenic regimens, except for the study of Gebbia et al (1994), which also included a comparison of the two agents in moderately emetogenic chemotherapy.…”
Section: Side-effectsmentioning
confidence: 99%
“…Nausea and vomiting is one of the major adverse effects of cytotoxic drugs and it is most frequently reported by the patients those who are undergoing chemotherapy for hematological and oncological malignancies like, ALL, Hodgkin's lymphoma (HL) and Non-Hodgkin's lymphomas (NHL) 1 .Without appropriate and effective prophylactic measurement severe nausea and protracted vomiting may results in severe dehydration, electrolyte abnormalities, malnutrition and aspiration of food materials leading to aspiration pneumonia and increased frequency of hospital admission. So, a very effective, well tolerated and potent antiemetic drug is mandatory for those patients who are receiving intensive chemotherapeutic agents 2 .…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades several drugs likemetochlorpropamide, levosulpride, steroids, phenothiazine and other compounds were randomly used to combat CRNV without any satisfactory results 1 .Moreover, the compounds had moderate efficacy and significant adverse effects, such as sedation and extra pyramidal symptoms 4 . Since mid1980s a major advancement had found in the development of antiemetic drugs 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of the serotonin antagonists ondansetron, granisetron and tropisetron has been compared in several trials and no significant differences have been shown (Campora et al, 1994;Gebbia et al, 1994;Stewart et al, 1995).…”
mentioning
confidence: 99%